"THE IMPACT OF CORPORATE GOVERNANCE APPLICATION ON THE QUALITY OF FINANCIAL REPORTS" "An Empirical Study on electric industry companies in the Republic of Iraq " - Sajjad Mohammed Ali; Lassaad Lakhal; Mushtak Al_Sabawy (Scholars Digest Publishing, 2023)
The research aims to determine the extent of the impact of corporate governance on the quality of financial reports in electric industry companies in the Republic of Iraq. The study utilized a descriptive-analytical research method, with the research population consisting of employees in electric industry companies within the Republic of Iraq. The research sample size was 357 individuals. The research findings concluded that there is a statistically significant relationship between the implementation of corporate governance practices and the quality of financial reports in electric industry companies within the Republic of Iraq. As a result, the research recommends the development of strong disclosure and transparency policies that adequately reveal financial information and relevant operations. This includes enhancing mechanisms of accountability.
Keywords: Corporate Governance, Financial Reporting Quality, Disclosure and Transparency, Empowerment and Participation, Accountability, Comprehensive Income Statement, Statement of Financial Position, Statement of Changes in Equity, Electric Industry Companies.